Design, synthesis and application of two-dimensional metal tellurides as high-performance electrode materials - Guo, Meng; Gu, Shaonan; Xu, Shuzheng; Lu, Jiani; Wang, Yinan; Zhou, Guowei (Frontiers in Chemistry, 2022)
Multifunctional electrode materials with inherent conductivity have attracted extensive attention in recent years. Two-dimensional (2D) metal telluride nanomaterials are more promising owing to their strong metallic properties and unique physical/chemical merits. In this review, recent advancements in the preparation of 2D metal tellurides and their application in electrode materials are presented. First, the most available preparation methods, such as hydro/solvent thermal, chemical vapor deposition, and electrodeposition, are summarized. Then, the unique performance of metal telluride electrodes in capacitors, anode materials of Li/Na ion batteries, electrocatalysis, and lithium-sulfur batteries are discussed. Finally, significant challenges and opportunities in the preparation and application of 2D metal tellurides are proposed.